Thirst Management among Patients with Hemodialysis by Sucking Ice Cubes: A Literature Review - Rhenanda Dewi Puspitasari Prasetyo; Hinin Wasilah (JIKO (Jurnal Ilmiah Keperawatan Orthopedi), 2022)
Thirst is the most common symptom burden among patients with hemodialysis. Thirst among patients with hemodialysis caused by fluid restriction lead to stress and depression, especially among patients who consume diuretics. This study aims to analyze the benefit of sucking ice cubes among patients with hemodialysis according to empirical studies in the last ten years. The articles were obtained from several databases such as Scopus, ProQuest, Google Scholar, ScienceDirect, and the National Library of Indonesia. There were five articles reviewed by the authors. According to the five articles, ice cubes effectively reduce thirst among patients with hemodialysis. Patients with hemodialysis can suck the ice cubes maximum of three to four times a day. Sucking the ice cubes can reduce thirst because it has a cold effect which can freshen and reduce the thirst longer. Nurses can provide and educate this alternative intervention which is effective to reduce thirst among patients with hemodialysis. Sucking the ice cubes can be conducted by the patients in the hospital also in the patient's home with the family's help.